2021
DOI: 10.1371/journal.pone.0251393
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthiness appraisals of faces wearing a surgical mask during the Covid-19 pandemic in Germany: An experimental study

Abstract: Background During the Covid-19 pandemic, the negative effects of wearing a mouth-nose cover (MNC) on interpersonal functioning have been discussed in public media but empirical studies on how wearing MNCs affect social judgements are sparse. In the present study, we investigated the effects of MNCs on trustworthiness appraisals, the influence of changes due to MNCs in evaluating joy, and the relationship between a social-cognitive appraisal bias and a participant’s characteristics. Methods All participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 44 publications
1
56
1
1
Order By: Relevance
“…Information from both the eye and mouth region is involved in trustworthiness and competence judgements (Dotsch & Todorov, 2012;Olivola & Todorov, 2010;Riggio & Riggio, 2010), so it is reasonable to assume that masks could lead to similar perceptual effects. In support of this, Marini et al (2021) found that transparent face masks did not have a significant effect on trustworthiness judgements, whereas opaque masks did affect trustworthiness judgements for some faces (specifically, they increased trustworthiness ratings for "untrustworthy" faces) (see also Biermann et al, 2021). Attractiveness judgements are influenced by facial symmetry (Rhodes, 2006) and contrast, particularly in the eye region (Killian et al, 2018).…”
Section: Face Coverings and Social Judgementsmentioning
confidence: 89%
See 2 more Smart Citations
“…Information from both the eye and mouth region is involved in trustworthiness and competence judgements (Dotsch & Todorov, 2012;Olivola & Todorov, 2010;Riggio & Riggio, 2010), so it is reasonable to assume that masks could lead to similar perceptual effects. In support of this, Marini et al (2021) found that transparent face masks did not have a significant effect on trustworthiness judgements, whereas opaque masks did affect trustworthiness judgements for some faces (specifically, they increased trustworthiness ratings for "untrustworthy" faces) (see also Biermann et al, 2021). Attractiveness judgements are influenced by facial symmetry (Rhodes, 2006) and contrast, particularly in the eye region (Killian et al, 2018).…”
Section: Face Coverings and Social Judgementsmentioning
confidence: 89%
“…Much of the data about masks and face processing reported to date was collected in the early months of the pandemic-for example, Biermann et al (2021) collected data between July and October 2020, when masks had been mandatory for three to six months in Germany (where the data was collected). At this point, most individuals in Western countries had relatively limited exposure to masks, so it is unsurprising that this unfamiliar perceptual occlusion disrupted face perception.…”
Section: Variability Of Effects Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study by Bierman et al (2021), a stronger negative bias was found in happiness and trustworthiness judgments of faces with masks for those who attribute less protective effect to masks, have a lower experienced risk concerning COVID-19 and those who see face mask wearing as a burden. Further, for trustworthiness appraisals, the negative bias was stronger for those who tend to comply less with the face mask wearing rules (Biermann et al, 2021). Further, face masks by themselves may also have negative associations with danger (e.g., pollution, disease) and covering face even by a non-mask fabric (e.g., scarf) may trigger the feelings of insecurity (i.e., someone is hiding true emotions or having bad and unclear intentions).…”
Section: Emotion Recognition: Effects Of Mask Patterns and Colormentioning
confidence: 93%
“…Now that the physical distance from others has increased drastically, it is possible that the psychological sense of distance with friends is also changing, and that it may be working positively or negatively for them. Particularly, living with a mask every day is likely to make it difficult to read facial expressions and understand emotions ( 17 ). That is, students' current school and family life is completely different from the lives they had prior to the pandemic.…”
Section: Introductionmentioning
confidence: 99%